Prevalence and Demographic Determinants of Anaemia and Its Correlation with Blood Group among Medical and Paramedical Students - Agarwal, Ajay Kumar; Katiyar, Ghansyam Das; Singh, Kashmir; Mahmood, Syed Esam; Khan, Swati; Sharma, Mahendra (National Journal of Community Medicine, 2018)
Background: Anaemia is a global health problem. Medical and para-medical students come from different regions, socio-economic status, cultural backgrounds and various geographical regions of country. This study was undertaken to find out prevalence and demographic determinants of anaemia, its correlation with blood group in medical and para medical students. Material and methods: This cross sectional study was conducted in 344 medical and para-medical students of Rohilkhand Medical College and hospital, Bareilly. A structured schedule was used to collect the information regarding anemia and blood group typing. Data was analysed using SPSS software. Chi-square test was applied. Results: The overall prevalence of anaemia was 29.07%. Prevalence was higher among female students (41.92%), among those aged between 25-26 years (75.00%) and among Muslims (40.54%). Prevalence of anaemia was higher among students having blood group A (33.33%) followed by group O (29.65%). Conclusion: Blood group exhibits a strong correlation with anemia. Early identification of anaemia and its modification among these medical and para medical students is required.